The Publishing of International Multilingual Lithuanian Periodicals (1904–1940) - Petreikis, Tomas (Knygotyra, 2019)
During 1904–1940, a total of 26 periodicals were published in Lithuania and in foreign countries in which the Lithuanian language was used alongside others. The demand for multilingual periodicals had emerged during the first part of the 20th c. as new cultural, economic, and political conditions took shape in Eastern and Central Europe. For the governments and businesses of Lithuania, Germany, Latvia, and Poland, the development of economic relations was of the biggest importance, and this process was to be stimulated using the multilingual publications that were being released in these countries. Also, particular importance was granted to the political cooperation of the Baltic States (Estonia, Latvia, and Lithuania). Cultural relations, on the other hand, were less expressed in the multilingual periodicals and not characterized by commercial success. For propaganda purposes, a considerable number of multilingual publications were released by Germany during the First World War. Apart from Lithuanian, these multilingual publications were marked by the use of German, English, Polish, French, Latvian, and Russian languages; among the rarer instances were Belarusian, Yiddish, and Estonian texts. The emergence of multilingual periodicals and the presence of the Lithuanian language in these publications reflected the international recognition of the Lithuanian nation and its state. It represented an understanding of multiculturalism and peculiar needs within the society and resembled the dialogue occurring across the political, economic, and cultural dimensions.